Biodistribution of N-lsopropyl-p-lodoamphetamine in the Rat Brain - Hoshi, H.; Jinnouchi, S.; Watanabe, K.; Ueda, T.; Kinoshita, K.; Yamaguchi, T. (Nuklearmedizin - NuclearMedicine, 1987)
The biodistribution of N-isopropyl-p-iodoamphetamine (IMP) was studied in the rat brain.131 l-labelled IMP was injected intravenously in awake animals. Activities in the brain of Sprague-Dawley rats were 2.68–3.22 (% dose/g) in the cortex and 0.59–0.66 (% dose/g) in the white matter at 1 min p. i. Activities in the cortex were slightly increased at 60 min p. i., while activities in the white matter increased markedly at 60 min and 6 h p. i. Therefore, the cerebral cortex-to-white matter ratio decreased from 5 to 1 within 60 min after injection. Autoradiograms of the rat brain at 1–10 min p. i. showed high contrasts. Activities were high in the cortex and low in the white matter, but homogeneous at 60 min – 6 h. IMP seems to be a useful agent for cerebral perfusion imaging in the early phase after injection. Knowledge of biodistribution of this agent is considered to be indispensable for the interpretation of images.Die Bioverteilung von N-Isopropyl-p-Jodamphetamin (IMP) wurde im Gehirn der Ratte untersucht. 131J-markiertes IMP wurde nichtanästhesierten Sprague-Dawley Tieren i. v. injiziert. Die Aktivitätskonzentration im Gehirn betrug 1 Min. nach der Injektion 2,68–3,20% injizierter Aktivität/g im Cortex und 0,59–0,66% injizierter Aktivität/g in der weißen Substanz. Bis zu 60 Min. p. i. stieg die Aktivität im Cortex leicht an. Die Konzentrationen in der weißen Substanz nahmen dagegen zwischen 60 Min. und 6 h p. i. deutlicher zu. Somit verminderte sich zwischen 1 und 60 Min. p. i. das Speicherverhältnis Cortex – weiße Substanz von 5 auf 1. Autoradiogramme des Rattenhirns zum Zeitpunkt 1 bis 10 Min. p. i. zeigten hohe Aktivitätskontraste. Hohe Ruheaktivitäten fanden sich im Cortex, niedrige in der weißen Substanz. 60 Min. bis 6 h p. i. war die Verteilung deutlich homogener. IMP erwies sich unmittelbar nach der Injektion als brauchbare Substanz zur Darstellung der Hirndurchblutung. Kenntnisse über die Bioverteilung dieser Substanz sind für die Interpretation der Befunde unabdingbar.